Perbaikan proses produksi dan ijin edar guna meningkatkan mutu produk unggulan daerah - Suprayogi, Suprayogi; Sabrina Sunyoto, Nimas Mayang; Syamsul Hadi, Mochammad; Fadhilah, Umi; El Afwa, Muthia; Nur Aziza, Nadya Lulu; Zulismar, Reni; Nareswari, Bernardia Filia; Firdausyi, Izzati Ardhan (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
KWT "Sri Tanjung" was one of the Women Farmers Groups (KWT) in Sukosari Village, Malang Regency. They produced "Jaselang" drinks (ginger, secang, alang-alang) and corn chips. KWT members produced the products with traditional technology and low quality of food safety and they did not have marketing license. The purpose of this service activities was to provide the education of KWT members in the form of training related with good product handling processes to ensure product safety, especially the Good Manufacturing Practices (GMP) and marketing license of National Food and Drug Agency. The method of implementing this community service were preparation, implementation, monitoring, and evaluation. The results of the activities showed that 100% of the participants could know the definition, benefits, and objectives of implementing GMP. Besides, after the implementation of the marketing license socialization, 100% of the participants knew the definitions, requirements, methods, and registered the marketing license. The activities increased the knowledge of KWT members regarding the implementation of GMP and marketing license.